A functional-precision analysis of the Vertical Comparator for the Calibration of geodetic Levelling Systems. (15th October 2020) - Kuchmister, Janusz; Gołuch, Piotr; Ćmielewski, Kazimierz; Rzepka, Janusz; Budzyń, Grzegorz
Highlights: We propose the original vertical comparator for the calibration of geodetic levelling systems. The developed and construction system is based on interferometric measurements. The measurement and calculation process is automated and based on an original program. Vertical comparator can be used to test digital geodetic levelling systems of different manufacturers. Abstract: Precise geodetic levelling measurements use a measuring set consisting of a precise digital level and digital (bar coded) levelling staffs. Such a measuring set enables automation of height measurement records and obtaining the accuracy of double-run levelling at the level of ±0.2 mm/1 km. Under the existing legislation (international and domestic) levels and levelling staffs should be subject to periodic tests followed by the issuing of calibration certificates. Such tests are carried out with the use of comparators and specialized measuring stations. The paper presents the development and construction of such an instrument, namely the Vertical Comparator for the Calibration of Levelling Systems (hereinafter referred to as VCCLS) in the Laboratory of Geodetic Technologies (LGT) of the Wrocław University of Environmental and Life Sciences (Pol. Uniwersytet Przyrodniczy we Wrocławiu ; hereinafter: UPWr). Presented and discussed in the paper are experimental and research works concerning the construction and functionality of the comparator as well as the environment conditions in the LGT. An analysis of the results of testing of two levelling systems: of Leica and Trimble companies allowed for defining the extended uncertainty of the comparator (at the confidence level of 95%), which amounted to ± 2.1 μm. The paper demonstrates the advantages of the original Vertical Comparator for the Calibration of geodetic Levelling Systems as compared to design solutions known from the professional literature. Designed and constructed at UPWr, the novel VCCLS is characterized by uncomplicated construction, simple adjustment of its interferometric measuring system and versatility as it can be used to test digital geodetic levelling systems which apply both digital and analog levelling staffs of different manufacturers (including Leica, Trimble, Topcon, Sokkia, Zeiss).